Rancang Bangun GPS Tracker Pada Kendaraan Bermotor Menggunakan SIM7000 NB-IoT Berbasis Arduino - Ana Febriana; Andi Ahmad Dahlan; Firdaus Firdaus (Elektron : Jurnal Ilmiah, 2021)
The rise of motorcycles today is in line with the increase in criminal acts such as motorcycle theft. Even though it is equipped with a security system such as a shutter key and ignition key, motorbikes can still be broken into by burglar specialists. When a motorcycle theft occurs, what the community can do is report the incident to the police and the community takes a long time to find the whereabouts of the missing motorcycle. Based on these problems, an additional security system was designed for Arduino-based motorcycles by utilizing GPS and SIM7000 modules. With the help of a simple application on the user's smartphone, this motorcycle security system can be tracked at any time even remotely. The results of this test obtained the coordinate points taken by the motorcycle during the route with the default time interval of 1 second. The coordinates obtained are displayed directly on google maps that are connected to the application and stored in the history application to anticipate if a motor vehicle theft occurs. The accuracy of taking coordinates on this tool is 85% when the quality of the network received is in good condition and 75% when the quality of the network received is in poor condition.